Design and Usability Evaluation of a Web-Based Edutainment for Grade VII Science: Task Performance and System Usability Scale Findings - Pamungkas, Nurhuda Budi; Sintaro, Sanriomi (Institut Teknologi dan Bisnis Bina Sarana Global, 2025)
This study designed and evaluated a browser-based edutainment prototype for Grade VII science (gravity and Newton’s laws). Usability was examined through task-performance metrics and the System Usability Scale (SUS). Thirty students at SMPN 27, Bandar Lampung, completed an eight-task scenario covering core flows: launching the app, entering and navigating the World Map, starting and stopping gameplay, and accessing Learn and Credits. Core navigation tasks showed high effectiveness with short median times (e.g., launch: 96.7% success, 6.53 s; enter World Map: 93.3%, 7.79 s). The in-level physics puzzle was purposely more demanding (83.3% success, 35.74 s; 0.52 errors per participant), indicating a need for clearer in-level cues. Perceived usability was excellent (mean SUS 87.42, SD 5.02). Overall, the prototype appears classroom-ready; targeted refinements inside levels (first-run micro-tutorials, stronger affordances, on-demand hints) should further smooth first-time play. Future work will examine multi-session learnability, broaden device/browser coverage, and link gameplay to learning outcomes via pretest–posttest designs.